Kinetics of silver dissolution in aqueous solutions of hydrochloric acid - Tuleshova, E. Zh.; Bayeshov, A.B.; Aibolova, G.K. (KSU publ., 2019)
In this article results of the kinetic regularities of the processes of electrochemical oxidation-reduction of silver in a solution of hydrochloric acid by the recorded potentiodynamic polarization curves method were presented. The electrochemical behavior of silver electrodes was studied by voltammetry on an SVA-1BM potentiostat to elucidate the mechanism of oxidations. The main polarization current-voltage curves were taken at a sweep rate of 10 mV/s and were recorded on a flat two-coordinate potentiometer of H 301/1. A silver rod was used as the working electrode; its working surface was the front part, the area of which was 4 mm2. The measurements were carried out in a three-electrode cell relative to the silver chloride electrode (E0 = +0.203 V). Platinum was used as an auxiliary electrode. Voltammograms are mainly obtained in the temperature range of 20–70 ºС (293–343 К), with potential sweep rates of 5–100 mV/sec. To clarify the mechanism of the processes occurring during the polarization by alternating current, the electrodes were subjected to cyclic polarization, i.e. the curves were recorded first in the direction of the cathode-anode, then the anode-cathode. The effect of electrolyte concentration and temperature, sweep rate on the electrochemical behavior of silver has been studied. The peculiarities of silver oxidation kinetics in an acidic medium were revealed. These data and the results of our previous studies serve as the theoretical foundations of electrode processes during the polarization of silver and other noble metals by alternating current and are prerequisites for the creation of new methods of metal extraction from waste solutions and wastewater and procedures for the synthesis of compounds for use in various industries. The following kinetic parameters were calculated to characterize the mechanism of the silver electro-oxidation: the ion transfer number (αn), the diffusion coefficient (D), the heterogeneous constant of the electrode process rate (Ks) and the effective energy of the activation process (Ea).
Keywords: potentiodynamic polarization curves; electrochemical behavior; silver; hydrochloric acid; electrode; concentration; temperature; electro-oxidation